2005
DOI: 10.1038/sj.embor.7400333
|View full text |Cite
|
Sign up to set email alerts
|

A conserved element in Myc that negatively regulates its proapoptotic activity

Abstract: Myc is an oncoprotein transcription factor that promotes cell proliferation and apoptosis. Analysis of highly conserved elements within vertebrate Myc proteins has been instrumental in defining the functions of the Myc protein. Here, we probe the role of a highly conserved, but little studied, element within the central region of c-Myc, termed 'Myc box III' (MbIII). We show that MbIII is important for transcriptional repression by Myc, and for transformation both in vitro and in a mouse model of lymphomagenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 19 publications
3
59
0
Order By: Relevance
“…Where indicated, 200 ng/mL trichostatin A (TSA) was added to the medium with 4HT. Tet-Off-Myc cells were treated with 2 Ag/mL tetracycline for 2 or 4 h; alternatively, cells were treated with the HDAC inhibitor MS-275 (0.3 to 4 Amol/L) for 8 h. RNA was then prepared and RT-QPCR was performed as described (5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where indicated, 200 ng/mL trichostatin A (TSA) was added to the medium with 4HT. Tet-Off-Myc cells were treated with 2 Ag/mL tetracycline for 2 or 4 h; alternatively, cells were treated with the HDAC inhibitor MS-275 (0.3 to 4 Amol/L) for 8 h. RNA was then prepared and RT-QPCR was performed as described (5).…”
Section: Methodsmentioning
confidence: 99%
“…We recently reported that a conserved, but little studied, element within Myc-Myc box III (MbIII)-is important for the ability of Myc to repress transcription (5). Here, we investigate how MbIII contributes to this process, and present evidence that MbIII functions, in part, by recruiting the histone deacetylase (HDAC) HDAC3 to chromatin.…”
Section: Introductionmentioning
confidence: 99%
“…This region is less conserved, with the exception of a motif called Myc box 3 (MB3) that is found in all Myc proteins from insects to vertebrates (note that the term "Myc box 3" has been applied to a different region by Herbst et al, 2005;. Although MB3 resembles a PEST domain, and hence might be expected to contribute to the degradation of Myc protein, its deletion does not affect Myc's half-life (Herbst et al, 2004); this region also does not seem to contribute to transcriptional regulation by Myc (Kato et al, 1990).…”
Section: To Molecularly Understand How Myc Controls Its Target Genes mentioning
confidence: 99%
“…MBI contains critical phosphorylation sites and is a region frequently mutated in Burkitt's Lymphomas (Bhatia et al, 1993;Bahram et al, 2000;Chang et al, 2000). The MBII region is essential for most biological functions, including transformation in all cell lines and mouse models reported (Stone et al, 1987;Oster et al, 2003;Herbst et al, 2005;Cowling et al, 2007). MBII is also a critical region for certain protein-protein interactions, including the interaction with an important co-factor in transformation, TRRAP (McMahon et al, 1998).…”
Section: Introductionmentioning
confidence: 99%